2017
DOI: 10.7717/peerj.3798
|View full text |Cite
|
Sign up to set email alerts
|

Allele specific expression and methylation in the bumblebee,Bombus terrestris

Abstract: The social hymenoptera are emerging as models for epigenetics. DNA methylation, the addition of a methyl group, is a common epigenetic marker. In mammals and flowering plants methylation affects allele specific expression. There is contradictory evidence for the role of methylation on allele specific expression in social insects. The aim of this paper is to investigate allele specific expression and monoallelic methylation in the bumblebee, Bombus terrestris. We found nineteen genes that were both monoallelica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…The identification of genes showing parent-of-origin expression in this study lays the ground work for future research to identify potential epigenetic mechanisms of allele specific expression in social insects. Genes showing allele specific expression and DNA methylation have been previously identified in B. terrestris (Lonsdale et al, 2017), and genes involved in the reproductive process have been shown to be differentially methylated between reproductive castes (Amarasinghe et al, 2014; Marshall et al, 2019). DNA methylation is the mechanism by which some genes are imprinted in mammals and plants (Scott and Spielman, 2006) and so investigation of parent-of-origin methylation in B. terrestris may be fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of genes showing parent-of-origin expression in this study lays the ground work for future research to identify potential epigenetic mechanisms of allele specific expression in social insects. Genes showing allele specific expression and DNA methylation have been previously identified in B. terrestris (Lonsdale et al, 2017), and genes involved in the reproductive process have been shown to be differentially methylated between reproductive castes (Amarasinghe et al, 2014; Marshall et al, 2019). DNA methylation is the mechanism by which some genes are imprinted in mammals and plants (Scott and Spielman, 2006) and so investigation of parent-of-origin methylation in B. terrestris may be fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…A competition phase then occurs between queens and workers, where some workers will become reproductive and produce their own haploid sons (Alaux et al 2006); this results in distinct reproductive worker castes within the colony. Multiple recent studies have highlighted B. terrestris as an ideal organism to assess methylation as a potential regulatory mechanism for reproductive caste determination (Amarasinghe et al 2014;Lonsdale et al 2017;Li et al 2018).…”
Section: Impact Summarymentioning
confidence: 99%
“…A competition phase then occurs between queens and workers, where some workers will become reproductive and produce their own haploid sons (Alaux et al , 2006), this results in distinct reproductive worker castes within the colony. Multiple recent studies have highlighted B. terrestris as an ideal organism to assess methylation as a potential regulatory mechanism for reproductive caste determination (Li et al , 2018; Lonsdale et al , 2017; Amarasinghe et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Methylation regulatory genes were identified in the bumblebee genome and have since been shown to have varying expression levels between queens, workers and drones (Li et al , 2018). Additionally, genes showing allele-specific methylation and gene expression have been identified and are enriched in reproductive related processes (Lonsdale et al , 2017). Most importantly, experimental changes in methylation in B. terrestris workers has been shown to alter levels of reproductive behaviour (Amarasinghe et al , 2014).…”
Section: Introductionmentioning
confidence: 99%